1974
DOI: 10.1161/01.cir.50.3.588
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Origin of One Pulmonary Artery from the Ascending Aorta

Abstract: SUMMARYSix patients with origin of one pulmonary artery from the ascending aorta are presented. Two are alive: a 21-year-old female, unoperated, with bilateral pulmonary vascular obstructive disease (PVO) and a 4-yearold girl who underwent successful correction at age 5 months. In addition, the data are reviewed from previous reports of 44 patients with this anomaly. Among the total of 50 patients, 42 had congestive heart failure in infancy. The right pulmonary artery arose anomalously in 44. A patent ductus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Clinically, these patients often present with progressive respiratory distress and evidence of congestive heart failure There is often a degree of cyanosis from the right to left shunting through the PFO of PDA and secondary to elevated end-diastolic pressure in the hypertensive, noncompliant right ventricle from increased pulmonary resistance [7,16]. Almost all patients had systemic or suprasystemic right ventricular pressure in our study.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Clinically, these patients often present with progressive respiratory distress and evidence of congestive heart failure There is often a degree of cyanosis from the right to left shunting through the PFO of PDA and secondary to elevated end-diastolic pressure in the hypertensive, noncompliant right ventricle from increased pulmonary resistance [7,16]. Almost all patients had systemic or suprasystemic right ventricular pressure in our study.…”
Section: Discussionmentioning
confidence: 69%
“…The full quantity output flows to the single lung attached to the right ventricle, and the other lung is exposed to unrestricted aortic blood flow and pressure. If this abnormal circulation is allowed to continue uncorrected, early development of pulmonary vascular obstructive disease can be expected [7,16,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without surgery, the mortality in patients with AOPA is extremely high, reaching as high as 80%. [2][3][4][5] This is due to severe, rapidly progressive pulmonary vascular disease and congestive cardiac failure. Both isolated AOLPA and that associated with other defects have been well described.…”
mentioning
confidence: 99%
“…Keane et al . [5] in their review found that histologically there was no significant pulmonary vascular obstruction in the majority of the 18 infants who died ; while significant changes, mainly in the systemic lung, were observed in six of the ten older children . Griffiths et al .…”
Section: Discussionmentioning
confidence: 97%